Analysis of Biological Learning Process Through Lesson Study by Using Transcript Based Lesson Analysis on Nervous System Material - Mira Fitriana; Hasanuddin Hasanuddin*; Wiwit Artika; Samingan Samingan; Safrida Safrida (Universitas Syiah Kuala, 2022)
Reflect on a lesson can be done with Lesson Study (LS). The application of lesson study using Transcript Based Lesson Analysis (TBLA) has not been explored further in Aceh. Therefore, it is necessary to add a new framework to analyze a learning practice with evidence-based analysis for improving teaching quality. The research aims to analyze the learning process, especially forming student concepts using TBLA-based LS. The Research method is mix method with typology concurrent triangulation identical sampling means quantitative and qualitative data obtained at the same time. The learning process was done in class xi Mipa 1 SMAN Modal Bangsa Aceh using the Modelling Instructions learning model with Neuron Phet Simulation media. Collection of data by audio and video recordings and observer observation sheets. Audio and video recordings are transcripted into conversational dialogue and analyzed by calculating the number of concept-forming keyword frequencies, length of sentences, and type of questions found during the learning process. These three parameters spell out their correlation to the formation of concepts. The results prove that there is a process of growth of ideas and forming the right concept by students, which means that teachers appreciate the thought process and the development of students’ ideas. Learning analysis using TBLA can lead teachers to investigate how students construct concepts, the reflection is necessary to do as the basis for the development of further learning